Use of Lymphatic Systems for Absorption of Nano-particles - Qarmout, Mr. Yousef A. M. (Asian Journal of Pharmaceutics (AJP), 2022)
The process of drug delivery through the lymphatic system is difficult and complex and also follows a physiological uniqueness system. There is an important role that the lymphatic pathways show in the transport of fluids outside the cell, and they can be avoided the first-pass metabolism of the lymphatic system is distinguished by its ability to assess disease states and progressive diseases-based lipids Nano-formulation in the lymphatic system. Solid lipid nanoparticles, for example, have extraordinary features that make them attractive candidates for lymphatic delivery. For colloidal carrier systems, these formulations are excellent because it has controlled release characteristics and provide greater stability of chemicals to drug molecules. Lipid-based Nano-formulations for absorption and distribution are wanted to be subject to interstitial obstruction during drug delivery regulation; there are factors such as the size of the particle, weight of the molecules, and charge of the surface depends on the absorption and distribution by the lymphatic system of the lipid-based nano-formulation, lipid forms important factors also affect the drugs delivery through the lymphatic system.